1979
DOI: 10.1139/o79-103
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the quaternary structure of reversibly immobilized alkaline phosphatase derivatives

Abstract: Escherichia coli alkaline phosphatase has been reversibly immobilized on Sepharose CL-4B through two different methods, both based on a disulfide linkage, under conditions selected to favour the coupling of the enzyme to the solid support through one covalent linkage. The quaternary structure of the reversibly immobilized subunit, produced by dissociation of the matrix-bound dimer, was examined by cross-linking with the bifunctional reagent dimethyl suberimidate. Following release from the solid support, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1981
1981
2003
2003

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Monomers of the wild-type enzyme have been obtained through a variety of techniques such as thiol reduction in the presence of urea (11), acid treatment (12), metal chelation, followed by incubation in 5% formamide (9), or by isolation of matrix bound monomers (13). However, the characterization of these monomeric forms of E. coli AP have been conducted under very specialized conditions.…”
mentioning
confidence: 99%
“…Monomers of the wild-type enzyme have been obtained through a variety of techniques such as thiol reduction in the presence of urea (11), acid treatment (12), metal chelation, followed by incubation in 5% formamide (9), or by isolation of matrix bound monomers (13). However, the characterization of these monomeric forms of E. coli AP have been conducted under very specialized conditions.…”
mentioning
confidence: 99%
“…Many of the anomalies may arise from poorly defined systems as far as metal and endogenous phosphate content are concerned. A recent study on immobilized monomeric and dimeric forms of alkaline phosphatase reversibly bound to Sephadex (138) showed that whereas the former binds only one Zn(I1) ion per subunit, the latter binds two under the same conditions, that is, four per dimer. This clearly indicates an interaction between subunits at the most basic level; namely, the influence of a large surface area of contact between monomers on the conformation and consequent properties of the individual subunits.…”
Section: Subunit-subunit Interactionsmentioning
confidence: 99%
“…One approach to understanding the function of quaternary structures in enzymes is to study the properties of single subunits and to compare them with those of the native oligomer. Chan (1970) introduced the use of immobilization techniques in order to study possible activity of the isolated subunits under conditions in which reassociation was prevented, and subsequent reports demonstrated the existence of active subunits bound to a solid matrix (Chan & Mawer, 1972;Grazi et al, 1973;Green & Toms, 1973;Chan, , 1974Fell & White, 1975;Bickerstaff & Price, 1976;Bruch et al, 1976;Chan & Mosbach, 1976;Carvajal et al, 1977;Gurne et al, 1977;Batlle et al, 1978;Chantler & Gratzer, 1978;Kochetov & Solovieva, 1978;Andersson & Mosbach, 1979;Arrio-Dupont & Coulet, 1979;McCracken & Meighen, 1979). The use of immobilized enzyme as a tool for evaluating subunit interactions has been reviewed (Chan, 1976a,b;Bickerstaff, 1980).…”
mentioning
confidence: 99%